Adjuvant therapy efficacy of Chinese drugs pharmaceutics for COPD patients with respiratory failure: a meta-analysis. Issue 4 (5th April 2019) - Liu, Chunqiu; Li, Yin; Wang, Xinqiu; Lu, Tong; Wang, Xuejing
Abstract : We performed a meta-analysis to evaluate the efficacy and safety of Western medicine combined with Tanreqing for patients with chronic obstructive pulmonary disease (COPD) and respiratory failure. We comprehensively searched several online databases from the times of their inception to November 2018. The trial quality was assessed using the bias risk tool recommended by the Cochrane library. Relative risks (RRs) and their 95% confidence intervals (CIs) for binary outcomes and weighted mean differences (MDs) with 95% CIs for continuous data were calculated. A fixed effect model indicated that integrated Tanreqing group experienced higher overall treatment effectiveness (RR = 1.23, 95% CI: 1.17–1.30, P =0.000). Pooled results from random effects models indicated the oxygen partial pressure of the test group was significantly higher than that of the control groups (MD = 9.55, 95% CI: 4.57–14.52, P <0.000). The carbon dioxide pressure of the test group was significantly lower than that of the control groups (MD = –6.06, 95% CI: –8.19 to –3.93, P =0.000). The lung function score of the test group was significantly higher than that of the control group (MD = 7.87, 95% CI: 4.45–11.29). Sensitivity analysis indicated that the data were statistically robust. Clinical effects of Western medicine combined with Tanreqing used to treat combined COPD/respiratory failure were better than those afforded by Western medicine; no serious adverse reactions were noted. However, publication bias was evident, and further trials with larger sample sizes are required.